What causes cross-industry differences of technical efficiency? An empirical investigation - Michael Fritsch; Andreas Stephan (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2004)
Using micro-level panel data of about 35,000 firms from the German Cost Structure Census, we analyze the differences of technical efficiency across industries. Technical efficiency is estimated by firms' fixed effects. One striking result is that the distribution of technical efficiency across industries is positively skewed. This is because the efficiency distribution is truncated at the lower end due to the least efficient firms which exit the market. We investigate the causes of technical efficiency differences across industries. Our econometric analyses provide evidence that capital and human capital intensity, the degree of vertical specialization as well as new firm formation rate are important for explaining the average technical efficiency of an industry. – – Anhand von Mikro-Daten für ca. 35.000 Unternehmen aus der deutschen Kostenstrukturstatistik analysieren wir Branchenunterschiede der technischen Effizienz. Dabei wird die technische Effizienz als ein unternehmensspezifischer fixer Effekt spezifiziert. Ein wesentliches Ergebnis besteht in dem Befund, dass die Verteilung der technischen Effizienz über die Branchen eine positive Schiefe aufweist. Der Grund hierfür ist offenbar darin zu sehen, dass die Effizienzverteilung innerhalb der Branchen jeweils am unteren Ende abgeschnitten ist, da die Unternehmen mit relativ geringer Effizienz aus dem Markt ausscheiden müssen. Nach den Ergebnissen unserer ökonometrischen Analyse spielen die Sachkapital- und Humankapitalintensität, das Ausmaß vertikaler Spezialisierung sowie die das Ausmaß an Marktzutritten für die Erklärung der durchschnittlichen technischen Effizienz einer Branche eine wesentliche Rolle.
Keywords: D24; L10; L11; 330; Technical efficiency; cross-industry study; efficiency distribution; Technische Effizienz; Branchenunterschiede; Effizienzverteilung; Technische Effizienz; Branche; Kostenstruktur; Schätzung; Deutschland